(untitled) (Physical Education, Health and Social Sciences, 2026)
Female domestic workers are those who provide services related to daily chores to the house of the employer, their job includes washing, cleaning, elderly care, baby sitting and cooking etc. statistics of Domestic work in Pakistan’s informal employment sector, is around 74%. Many women turn toward this sector of employment for survival, but unfortunately there are no proper labor laws implemented that provide security to such jobs. However, while carrying out their responsibilities, these women encounter significant economic and societal hardships. The aim of this research is to analyze the socio-economic challenges faced by female domestic workers in District Abbottabad and to identify the coping strategies adopted by the women. The study universe is District Abbottabad and female domestic workers were chosen as the target population. District Abbottabad is a district of the Pakistani province of Khyber Pakhtunkhwa. This research used a combination of qualitative and quantitative techniques to collect primary data. Participants were chosen using a simple random sampling method. Total of 90 individuals were selected. The research findings reveal that a majority (98%) of women employed in domestic work having a monthly income below 10,000, Just 1% of respondents reported earning more than this amount. Furthermore, the study highlights the prevalence of a significant 82% of respondents who are open to various forms of social mistreatment in various aspects of their lives.